2014
DOI: 10.1080/09644016.2014.923632
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy innovation: a sociotechnical transitions perspective

Abstract: Seeking to develop a novel understanding of how climate policy innovations emerge and spread, we conceptualize three types of CPIs genuinely original, diffusion based and reframing based and relate these to the socio-technical transitions literature, particularly the multi-level perspective that explains change through interaction between . Selected climate-related transport policies in Finland, Sweden and the United Kingdom are used to illustrate five hypotheses that connect these concepts from the multi-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 41 publications
(26 reference statements)
0
22
0
5
Order By: Relevance
“…Third, developed countries generally have fewer problems with knowledge/scoping issues. Overall, these points are indicative of the differences in the capacity of public sectors, with agencies in developing countries generally being less adequately resourced [35,63,67,74,97]. In terms of scale, international initiatives were more prone to discursive issues, largely due to the complexity of international negotiations, but less vulnerable to specific environmental factors due to the general nature of their scope [100,101,105,106].…”
Section: Comparison Of Policy Failure In Different Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, developed countries generally have fewer problems with knowledge/scoping issues. Overall, these points are indicative of the differences in the capacity of public sectors, with agencies in developing countries generally being less adequately resourced [35,63,67,74,97]. In terms of scale, international initiatives were more prone to discursive issues, largely due to the complexity of international negotiations, but less vulnerable to specific environmental factors due to the general nature of their scope [100,101,105,106].…”
Section: Comparison Of Policy Failure In Different Contextsmentioning
confidence: 99%
“…Case studies in Finland, Italy, the West Balkans and Australia indicated that failure may result where policies are not well developed, are not implemented fully, are not politically popular, or go against a prevailing political agenda [41,47,48,67,71,74,79,[92][93][94]. Dominant interests, such as extractive industries, may influence what is politically feasible, resulting in a failure to deliver sustainability [41,42,44,46,49,58,60,73,81,93,[95][96][97]. An unstable political climate or corruption can further limit success [37,49,53,56,59,67,74,77,96,98].…”
Section: Interrelated Structural Causesmentioning
confidence: 99%
“…A distinction can be made between genuinely new (i.e., the first manifestation anywhere), and new in a particular bounded territory but possibly existing in a similar format or manner elsewhere. Borrowing from Upham and colleagues [55], we can call the former an original innovation and the latter a diffusion-based innovation. "New" is also relative to particular time scales.…”
Section: Innovations Definedmentioning
confidence: 99%
“…Policy innovation can be depicted as a rather broad concept referring to novelty in both policy processes and their outputs (Jordan and Huitema, 2014a;Upham et al, 2014). This means that (1) policy innovation as a process change may, for example, link to increased flexibility for policy, encouraging substance related experimentation, or (2) policy experiments can lead to or refine policy innovations as an output.…”
Section: Policy Experiments For Climate Policy Innovation or Vice Versamentioning
confidence: 99%
“…This means that (1) policy innovation as a process change may, for example, link to increased flexibility for policy, encouraging substance related experimentation, or (2) policy experiments can lead to or refine policy innovations as an output. These outputs can be new policy goals, new policy instruments, or new types of leverage mechanisms or implementing organisations (Jordan and Huitema, 2014a;Upham et al, 2014). For example, a series of experiments prepared the ground for adopting the European emission trading scheme (Hildén 2014).…”
Section: Policy Experiments For Climate Policy Innovation or Vice Versamentioning
confidence: 99%